Preservation preferences for cultural relics in traditional Chinese museums: balancing tradition and technology - Liu, Jun; Abdul Ghafar, Maszura; Ab Halim, Adlina (Faculty of Art and Design, 2025)
Traditional Chinese museums face the dual challenge of preserving fragile cultural relics and engaging modern audiences. Current preservation methods often emphasize either physical conservation or digital representation; however, an integrated approach may be more effective. This study examined the state of cultural relic preservation in Chinese museums, highlighted key limitations of current practices, and explored the potential of integrating Mixed Reality (MR) and Human-Exhibition Interaction (HEI) to enhance preservation outcomes. By focusing on both artifact safety and visitor engagement, this research identified optimal preservation strategies for sustaining cultural heritage in China. Additionally, this paper proposed a conceptualization that leverages advanced technologies and interactive methods to address contemporary challenges while respecting traditional conservation philosophies.